The beauty of us - Proby, Kristen (Proby, Kristen. Fusion series, 2017)
Riley Gibson knows having her restaurant, Seduction, on the Best Bites TV network could be the big break she's been waiting for. But the idea of having an in-house show on a regular basis is a whole other matter. Convincing Mia, her best friend and head chef, that having cameras in her kitchen every day is a good idea is daunting. When Riley meets Trevor Cooper, the show's executive producer, she's stunned by their intense chemistry. At first his sole intention was to persuade Riley to do the show. But can he convince her that he's interested in Riley for himself?